Efektivitas Unit Pembelajaran Berbasis Guided Inquiry Laboratory (GIL) untuk Meningkatkan Keterampilan Berpikir Kreatif - Herning Nurdiana; Sajidan Sajidan; Maridi Maridi (Universitas Indraprasta PGRI Jakarta, 2021)
The purpose of this study is to see the effectiveness of the GIL-based human digestive system unit learning to improve students' creative thinking skills. The study used a quasi-experimental non-equivalent control group design which was carried out during the Covid-19 pandemic by distance learning. The research subjects were junior high school students in class VIII even semester of the 2020/2021 academic year which were divided into 2 classes, namely the experimental class and the control class. The results of this research and development stated that the GIL-based human digestive system unit learning can improve students' creative thinking skills. The results of the independent sample t-test from the gain score of the experimental class and the control class obtained significance of 0.000, meaning that there was a difference between the score before and after the unit learning was given, so it can be concluded that the use of GIL-based learning unit was effective for improving students' creative thinking skills. The total effect caused by the use of GIL-based learning units was carried out using an effect size analysis with cohen’s d of 1.01, which implied that the GIL-based unit learning had a great influence in improving students' creative thinking skills.